Teaching English to the world : history, curriculum, and practice - Braine, George (L. Erlbaum Associates, 2005)
A collection of English language teaching (ELT) histories, curricula, and personal narratives from non-native speaker (NNS) English teachers worldwide. Each chapter describes first the history of English language teaching in a country, then the current ELT curriculum, followed by the biography of an English teacher of that country.